EXPLOITATION OF HUB PROTEINS AS DRUG TARGETS FOR MYCOBACTERIUM TUBERCULOSIS H37RV - ABDUL-JALIL, ASRA’A A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Mycobacterium tuberculosis (TB), a causative agent of TB, increased the resistance to most drugs in use and coinfection with HIV. It needs the new drug(s), the latter should be special candidate targets. Methods: Hub proteins were studied (Rv2198c, Rv2507, and Rv3763) which had very high connected partners. These were modeled to be used for screening chemical databases. Results: The proteins were found to be with increased low-complexity regions especially at the amino ends, they exhibited primary level (layers) of interactions and involved in secondary and more levels of interactions. Conclusions: The proteins with high interacting partners would be good targets as their disruption will disturb the cellular functions. The chosen targets (Rv2198c, Rv2507, and Rv3763) have very high interactions at a different level (layers), they were modeled to be used in survey of chemical databases.